Promoting Foreign Investment in Fragile and Conflict-Affected Situations - Whyte, Robert (World Bank Group, Washington, DC, 2014)
Fragile and conflict-affected situations might appear incapable of attracting significant flows of foreign investment due to their often negative international images and weak enabling environments. However, during the last eight years, foreign investment into these economies has grown almost three times more quickly than flows into the rest of the world, albeit from a very low starting point. Untapped natural resources, reconstruction needs, and severely underserved consumer demand present domestic and foreign investors with significant opportunities, many of which continue to go unrealized. This note provides guidance to investment policymakers and promoters in fragile and conflict-affected situations, whose work is needed to bring those opportunities to fruition.